Synergistic Antibacterial and Antibiofilm Activity of the MreB Inhibitor A22 Hydrochloride in Combination with Conventional Antibiotics against Pseudomonas aeruginosa and Escherichia coli Clinical Isolates - Anastasia Kotzialampou; Efthymia Protonotariou; Lemonia Skoura; Afroditi Sivropoulou (International Journal of Microbiology)
In the era of antibiotic resistance, the bacterial cytoskeletal protein MreB is presented as a potential target for the development of novel antimicrobials. Combined treatments of clinical antibiotics with anti-MreB compounds may be promising candidates in combating the resistance crisis, but also in preserving the potency of many conventional drugs. This study aimed to evaluate the synergistic antibacterial and antibiofilm activities of the MreB inhibitor A22 hydrochloride in combination with various antibiotics. The minimum inhibitory concentration (MIC) values of the individual compounds were determined by the broth microdilution method against 66 clinical isolates of Gram-negative bacteria. Synergy was assessed by the checkerboard assay. The fractional inhibitory concentration index was calculated for each of the A22-antibiotic combination. Bactericidal activity of the combinations was evaluated by time-kill curve assays. The antibiofilm activity of the most synergistic combinations was determined by crystal violet stain, methyl thiazol tetrazolium assay, and confocal laser scanning microscopy analysis. The combined cytotoxic and hemolytic activity was also evaluated toward human cells. According to our results, Pseudomonas aeruginosa and Escherichia coli isolates were resistant to conventional antibiotics to varying degrees. A22 inhibited the bacterial growth in a dose-dependent manner with MIC values ranging between 2 and 64 μg/mL. In combination studies, synergism occurred most frequently with A22-ceftazidime and A22-meropemen against Pseudomonas aeruginosa and A22-cefoxitin and A22-azithromycin against Escherichia coli. No antagonism was observed. In time-kill studies, synergism was observed with all expected combinations. Synergistic combinations even at the lowest tested concentrations were able to inhibit biofilm formation and eradicate mature biofilms in both strains. Cytotoxic and hemolytic effects of the same combinations toward human cells were not observed. The findings of the present study support previous research regarding the use of MreB as a novel antibiotic target. The obtained data expand the existing knowledge about the antimicrobial and antibiofilm activity of the A22 inhibitor, and they indicate that A22 can serve as a leading compound for studying potential synergism between MreB inhibitors and antibiotics in the future.